Neural Mechanisms of Evidence Accumulation Selection for Flexible Decision Making - Uka, Takanori (Brain and nerve = Shinkei kenkyū no shinpo, 2025)
Multiple mechanisms are involved in flexible decision making, including relearning and the instantaneous switching of decisions depending on the environment. These mechanisms can be elucidated by integrating psychophysical, neurophysiological, and computational approaches. The flexibility of evidence accumulation necessary for instantaneous decision switching is supported by the mechanism of accumulating and discarding unnecessary information, which can be observed in the changes in decision-related activities in the LIP cortex as well as in other areas. The molecular mechanisms underlying the impairment of flexible decision-making are also discussed.